Penggunaan Media Sosial Instagram sebagai Alat Kampanye Partai Solidaritas Indonesia pada Pemilu Legislatif 2024 di Jakarta - Milenia Ferlihanisa; Endang Sulastri (Lembaga Pengembangan Kinerja Dosen, 2025)
The Indonesian Solidarity Party (PSI) distinguishes itself as the sole political party actively promoting its platform through mainstream media. Social media has become integral to political campaigns in Indonesia, with PSI leveraging these platforms more effectively than its contemporaries since its establishment in 2014. PSI sought to position politics as an engaging activity for diverse audiences and to reduce political apathy among young people. The research method used by the researcher was a qualitative descriptive-analytical approach, utilizing the theory of Harold D. Laswell's concepts of new media and political communication (propaganda). Thus, the results of the research that has been conducted, it can be concluded that, (1) PSI is able to establish itself as a party that is closely related to young people and digital; (2) Instagram is PSI's main platform that focuses on attracting the sympathy of young people, becoming the most effective platform in conveying political messages visually and audio-visually, (3) In the elections for the Indonesian House of Representatives and the Jakarta Province DPR D, PSI obtained an increase in votes compared to the 2019 Election, (4) PSI's political communication has characteristics that prioritize party communication with a youthful style and the capacity of figures.